Missionaries and modernity. Education in the British Empire, 1830-1910. By Felicity Jensz. (Studies in Imperialism.) Pp. viii + 278. Manchester: Manchester University Press, 2023. £25 (paper). 978 1 5261 7443 7 - Kinghorn, Alice (The journal of ecclesiastical history, 2025)
Missionaries and modernity. Education in the British Empire, 1830-1910. By Felicity Jensz. (Studies in Imperialism.) Pp. viii + 278. Manchester: Manchester University Press, 2023. £25 (paper). 978 1 5261 7443 7 - Volume 76 Issue 3